Predictive Validity of Basic Education Certificate Examination Compulsory Cross-Cutting Subjects in Senior School Examination in Kwara State, Nigeria (Impact: Journal of Transformation, 2024)
A justification for using any test result for its intended purpose is the ability of the items tomeasure the earlier set objectives which is construed as validity; a psychometric property of agood test cannot be over emphasized. The predictive strength of the Basic Education CertificateExamination Cross-cutting subjects in predicting students’ performance in both internal SeniorSecondary School I, Senior Secondary School II, and external examination (Senior SecondaryCertificate Examination) in Kwara State was examined in this paper. The study employedlongitudinal and ex-post-facto design. The population of this study consists of senior secondarystudents in Science, Art and Commercial departments that sat for the compulsory cross-cuttingsubjects in Basic Education Certificate Examination, internal promotional examination both inSenior Secondary School I, Senior Secondary School II and as well as Senior Secondary SchoolCertificate Examination in Kwara State between 2015/2016 – 2018/2019 academic sessions.Purposive random sampling technique was employed to sample 1200 [712 (59.3%) male and 488 Impact: Journal of Transformation Vol. 7 (2) 2024, ISSN 2617-5576(40.7%) female] students that have complete records of their scores across the years. Proformawas used to collect the respondents’ scores and were transformed to continuous form. The BasicEducation Certificate Examination and Senior Secondary Certificate Examination arestandardized examinations; hence the results are assumed to be satisfactory. However, scoresfrom teacher made tests/internal promotional examinations were standardised (t-score). Thecollected data were analysed with simple linear regression. Findings show that the BasicEducation Certificate Examinations were a good performance predictor for the Senior SecondaryCertificate Examinations. The study recommended that the general public and stakeholders retaintheir trust in and embrace the Basic Education Certificate Examination as a strong predictor ofstudents' academic performance.